2019
DOI: 10.3389/fnins.2019.00806
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity in Children With Low-Function Autism Spectrum Disorders

Abstract: Neuroimaging studies have shown that autism spectrum disorders (ASDs) may be associated with abnormalities in brain structures and functions at rest as well as during cognitive tasks. However, it remains unclear if functional connectivity (FC) of all brain neural networks is also changed in these subjects. In this study, we acquired functional magnetic resonance imaging scans from 93 children with ASD and 79 matched healthy subjects. Group independent component analysis was executed for all of the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 46 publications
5
19
0
Order By: Relevance
“…Recent studies of structural and functional brain networks in patients with ASD suggest that cognitive deficits may be attributed to abnormal connections between different brain regions (such as the superior occipital gyrus) [45][46][47][48]. Consistent with the results of our study, the superior occipital gyrus of participants with autism showed significant abnormalities as the task complexity increased when participating in the test task compared with the normal control group [45].…”
Section: Superior Occipital Gyrussupporting
confidence: 90%
“…Recent studies of structural and functional brain networks in patients with ASD suggest that cognitive deficits may be attributed to abnormal connections between different brain regions (such as the superior occipital gyrus) [45][46][47][48]. Consistent with the results of our study, the superior occipital gyrus of participants with autism showed significant abnormalities as the task complexity increased when participating in the test task compared with the normal control group [45].…”
Section: Superior Occipital Gyrussupporting
confidence: 90%
“…In depressed patients, reduced activation in the right middle frontal gyrus and increased activation in the amygdala and hippocampus were associated with memory suppression involving negatively valenced stimuli 41 . Reduced activation in the inferior frontal gyrus and supramarginal gyri were related to though suppression 42 .…”
Section: Neuroimaging Findings On Impulsivity and Thought Suppressionmentioning
confidence: 94%
“…To exemplify this idea, we can consider research in neurodevelopmental disorders, which has often focused on characterizing trait-dependent sources of variance. Research on autism spectrum disorder (ASD), which is characterized by impairments in social communication and restrictive, repetitive behaviors, points to distinct FC patterns that distinguish ASD from typically developing controls across rest and task ( Easson et al, 2019 ; Hull et al, 2017 ; Long et al, 2016 ; Xu et al, 2019 ). Less frequent, however, are studies that characterize both task-specific (state) and disorder-specific (trait) effects within the same sample.…”
Section: Concurrent Changes Of State and Trait Neurodevelopmental Varmentioning
confidence: 99%